Private equity investment committee paper on biotelemetry - value creation strategy and operating model - schofen, Lukas Raphael (2020)
Based company focused on providing remote cardiac monitoring services, clinical trial research services, glucose monitoring services and origina lequipment manufacturing. The herein proposed value creation strategy and the forecaste operating model, both base don thorough analysis of the company and the market sit operatesin, are intended to support the potentialle veraged buy out.